2017
DOI: 10.1080/21551197.2017.1391732
|View full text |Cite
|
Sign up to set email alerts
|

Whey Protein Supplementation Improves Rehabilitation Outcomes in Hospitalized Geriatric Patients: A Double Blinded, Randomized Controlled Trial

Abstract: Whey protein supplementation (WPS) has been shown to improve functional outcomes in populations that are able to participate in high-intensity resistance training. The purpose of the study was to evaluate the efficacy of WPS on rehabilitation outcomes in a frail, hospitalized elderly population. Men and women (n = 47) were randomly assigned to either a control group or WPS group for the length of their hospital stay. Several functional and serum measures were determined pre- and post-intervention. WPS signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(67 citation statements)
references
References 39 publications
1
64
1
Order By: Relevance
“…As well as exercises, nutritional interventions are proved to be important aspects. There are several studies that showed the additive effects of supplementation with protein [ 56 , 57 ], amino acids [ 58 ] to exercise intervention.…”
Section: Prevention Of the Onset And Progression Of Lsmentioning
confidence: 99%
“…As well as exercises, nutritional interventions are proved to be important aspects. There are several studies that showed the additive effects of supplementation with protein [ 56 , 57 ], amino acids [ 58 ] to exercise intervention.…”
Section: Prevention Of the Onset And Progression Of Lsmentioning
confidence: 99%
“…However, the PP analysis did not change the conclusions considerably, but the statistical power was also lower. A study with older hospitalised adults given PrS (24 g/d) and RT or RT only showed positive effects of PrS during the length of hospital admission which was > 20 d for both groups (58) . Thus, the short length of hospital stay for all participants in the present study (median of 5 d) may have blunted the chance of finding positive effects of the greater difference in protein intake between groups looking only at the hospitalisation period.…”
Section: Discussionmentioning
confidence: 94%
“…Because nutrition supplementation decreased readmission rate, an indirect measure of subacute/chronic improvement of the heart, it might be that such patients benefited significantly more from the long‐term nourishment of their heart and body so that after discharge, they stayed healthier and were not readmitted. Furthermore, protein supplementation has been shown to improve muscle mass and outcomes among patients in rehabilitation centers . Therefore, an effective modality of preventing adverse outcomes might be ongoing surveillance and identification of PEM among the U.S. populace in the community and provision of optimal nourishment, thereby keeping them away from rehospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, protein supplementation has been shown to improve muscle mass and outcomes among patients in rehabilitation centers. 46,47 Therefore, an effective modality of preventing adverse outcomes might be ongoing surveillance and identification of PEM among the U.S. populace in the community and provision of optimal nourishment, thereby keeping them away from rehospitalization. Studies are urgently needed to investigate the effect of such community intervention studies.…”
Section: Discussionmentioning
confidence: 99%